Salvage surgery for locoregional recurrence or persistent tumor after high dose chemoradiotherapy for locally advanced non-small cell lung cancer. (April 2016) - Dickhoff, C.; Dahele, M.; Paul, M.A.; van de Ven, P.M.; de Langen, A.J.; Senan, S.; Smit, E.F.; Hartemink, K.J.
Highlights: Treatment of locoregional recurrence after chemoradiotherapy is challenging. Available data is heterogeneous and hampers multidisciplinary decision making. We report salvage surgery can be performed with acceptable morbidity and mortality. Compared to other treatment options, salvage surgery can offer good survival. Abstract: Objectives: Curative intent treatment options for locoregional recurrence or persistent tumor after radical chemoradiotherapy for locally-advanced non-small cell lung cancer (NSCLC) are limited. In selected patients, surgery can be technically feasible, although it is widely believed to be hazardous. As data regarding the outcome of this approach is sparse, we evaluated our institutional experience with salvage surgery. Materials and methods: Patients with a pulmonary resection for in-field locoregional recurrence or persistent tumor after high dose chemoradiotherapy (≥60 Gy) for the treatment of non-small cell lung cancer, were identified and retrospectively analyzed. Results: A total of 15 patients treated between January 2007 and August 2015 were eligible for evaluation. In 13 patients (87%), the indication for surgery was a locoregional recurrence, while 2 patients had persistent tumor. The prior median radiotherapy dose was 66 Gy (range 60–70). All patients underwent an anatomical resection, with 8 patients having a pneumonectomy, and all pathological specimens revealed the presence of viable tumor. The in-hospital morbidity rate was 40% (6 patients), and the 90-day mortality rate was 6.7% (1 patient). Median follow-up was 12.1 months. The estimated median overall and event-free survivals were 46 months and 43.6 months, respectively. Conclusion: Salvage surgery for locoregional recurrence or persistent tumor after high dose chemoradiotherapy, resulted in acceptable morbidity, mortality and promising outcome. It should be considered as a treatment option for selected patients.